Determination of organophosphorus pesticides by dispersive liquid-liquid microextraction coupled with gas chromatography-electron capture detection. - Sanagi, Mohd Marsin; Mokhtar, Siti Umairah; Wan Ibrahim, Wan Aini; Miskam, Mazidatulakmam (Malaysian Society of Analytical Sciences (ANALIS), UKM, 2011)
A simple, rapid and sensitive method termed as dispersive liquid–liquid microextraction (DLLME) combined with gas chromatography-electron capture detector (GC-ECD) was developed for the determination of selected organophosphorus pesticides (OPPs) namely chlorpyrifos, dimethoate and diazinon in water sample. In this method, a mixture of carbon disulfide, CS2 (extraction solvent) and methanol (disperser solvent) was rapidly injected using syringe into the 5.00 mL water sample to form a cloudy solution where the OPPs were extracted into the fine droplets of extraction solvent. Upon centrifugation for 3 min at 3500 rpm, the fine droplets were sedimented at the bottom of the centrifuge tube. Sedimented phase (1μL) was injected into the GC-ECD for separation and determination of OPPs. Important extraction parameters, such as type of disperser solvent, volume of extraction solvent and volume of disperser solvent were investigated. The optimized conditions for DLLME of the selected OPPs were methanol as disperser solvent, 30 μL of extraction solvent (CS2 ) and 1.0 mL of disperser solvent (methanol). Under the optimum extraction conditions, the method showed good linearity in the range of 0.1 to 1.0 μg/mL with correlation coefficient (r 2 ), in the range of 0.9976 to 0.9994 and low limits of detection (LOD) between 0.047 and 0.201 μg/mL. The proposed method provided acceptable recoveries (72.67- 144%) with good RSDs ranging from 2.74% to 7.48%. This method was successfully applied to the determination of OPPs in water samples obtained from a golf course and chlorpyrifos and diazinon were detected at concentration 0.18 μg/mL and 0.07 μg/mL, respectively.